Adoption of Conservation Agricultural Practices among Maize Farmers: An Alternative Livelihood to Mitigate Climate Change Impact in Bawku Municipality, Ghana - Bawa, Alhassan; T. Jamedu, Abu (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2021)
The plight of farmers are worsening by the impact of climate change. This is evident in all agro-ecological zones in Ghana. Warming and variability in rainfall pattern is causing floods and long dry spells of drought with resultant effects of reduced food crop and livestock production. Conservation Agricultural (CA) practices was therefore introduced to address the challeges of conventional tillage. CA has therefore been identified as a substitute to conventional agriculture for sustainable agricultural productivity. The objective of the study was to assess the rate of adoption of CA practices in the Bawku Municipality in the Upper East region of Ghana. The study was conducted in the Bawku Municipal area of Ghana. The research design used for the study was the mixed methods. The purposive sampling technique was used Ito select the Bawku Municipality as the major area where agricultural conservation practices occurs in the Upper East region. The simple random sampling technique was used to select ten (10) communities in the Municipality, whilst the systematic random sampling was used to select forty (40) respondents from each community for the study. The target population for the study was maize farmers in the Bawku Municipality. In all, a total of 358 respondents were interviewed for the study. Data was taken on socio-cultural and socio-economic characteristics of respondents. Data analysis was done using the Statistical Package for Social Sciences (SPSS). Descriptive statistics, such as frequencies, percentages, and means were computed. Cross tabulations of variables were also computed and the chi-square tests used to establish relationships. The study revealed that age, sex, level of education, religion, household size, government policy, access to credit, source of income, farm size, and access to extension services were found to have significantly influenced adoption of CA practices. The results of the study indicated that majority of farmers were aware and had knowledge about CA practices. “No-tillage with cover crops, minimum tillage with cover crops, and crop rotation with cover crops” were the main practices of conservation agriculture in the study area. The study further revealed that majority of the farmers indicated that the practices of conservation agriculture reduces soil erosion, increases soil fertility, increases soil organic matter and improves agricultural productivity. The survey also reveals that 81% of farmers adopted CA practices in full. It is recommended that the Ghanaian government should boost CA practices by instituting an annual nation award scheme to award hardworking CA practioners in Ghana.